Ectopic expression of VyCIPK1 gene, isolated from wild grape Vitis yanshanesis J, X. Chen., confers the tolerance to salt in transgenic tobacco. Issue 1 (31st December 2022) - Zhu, Ziguo; Dai, Lingmin; Chen, Guangxia; Yu, Guanghui; Li, Xiujie; Han, Zhen; Li, Bo
ABSTRACT: Calmodulin-like interacting protein kinases play an important role in plant response to abiotic stresses and development. But the role of the CIPK gene in grapevine is unknown. In this study, VyCIPK1, isolated from the Chinese wild grape V. Yanshanesis, was strongly induced by salt stress. Overexpressing VyCIPK1 could induce AOC and AOS, and result in notably increased jamonate levels in tobacco. Under salt stress, transgenic plants showed higher germination rate, leaf number, and fresh weight than wild-type plants. Moreover, transgenic plants displayed higher chlorophyll content, catalase activity, peroxidase activity, superoxide dismutase activity, and lower malondialdehyde content, H2 O2, and O 2- content than that of wild type under salt stress conditions. And the stress-related genes, including ERD10C, ERD10D, LEA5, POD, SOD, and CAT, were up-regulated in transgenic plants. Our founding demonstrated that the VyCIPK1 has the potential for grape molecular breeding of salt tolerance as a candidate gene.